Strategi Lembaga Takmir Masjid Nahdlatul Ulama (LTM NU) Temanggung Dalam Mencegah Radikalisme Agama - Ibda, Hamidulloh; Saifuddin, Khamim (el Buhuth: Borneo Journal of Islamic Studies, 2019)
The background of this research is the potential for religious radicalism in mosques in Temanggung Regency. They are a radical group that has several ways to control the mosque. This article describes the strategy of the Mosque Organizers Institution Nahdlatul Ulama (LTM NU) of Temanggung in preventing religious radicalism in the mosque. This study uses a descriptive qualitative approach with data collection methods namely interviews and observations. The results of the study stated that there were several strategies carried out by LTM NU of Temanggung in preventing radicalism. First, strengthening the management of mosque takmir refers to Aswaja Annahdliyah’s Islamic values. Second, revitalization of idarah, imarah, and ri’ayah management. Third, revamping the management structure of the mosque. Fourth, mobilizing the spirit of religious leaders to strengthen moderate Islamic studies. Fifth, the movement of NU coins (koin NU) in the mosque. Sixth, assisting the mosque when there are problems or not. Seventh, synergy between the Autonomous Agency (Banom) and institutions under NU. Eighth, the mosque’s clean movement. Ninth, identify local lector who are preachers at the mosque. There are several challenges and opportunities in implementing the strategy. The first challenge is the low understanding of the organizational management of mosque takmir. Second, limited religious knowledge from the mosque manager. Third, the structure of Aswaja Annahdliyah teachings has not been structured. Fourth, the massive offer of radical Islamic activities in NU mosques. Fifth, the doctrine is strong about the strategy of mastering mosques from radical groups. Sixth, infiltration of individuals / radical Islamic organizations. Seventh, the strong funding from abroad in the construction of mosques. The opportunity, first is the strong family culture in the community. Second, awareness of the dangers of radicalism. Third, the dominance of NU residents in the mosque’s takmir structure. Fourth, the massive implementation of mosque takmir training. Fifth, the existence of Islamic religious instructors in the villages dominated by NU residents. Sixth, the implementation of the competition for destitution management. Seventh, program support from autonomous body (Banom) / NU institutions. The impact of this strategy to prevent religious radicalism gave birth to the awareness of takmir officials to guard mosques from radical groups. While in the short term, the management of the mosque takmir is set up to 90 percent of the total mosques that have joined LTM NU Temanggung, and there are dozens of mosques that will join LTM NU of Temanggung.